Genome characterization of Enterococcus lactis strain isolated from bovine subclinical mastitis - Cerioli, María Florencia; Fernandez, Franco Daniel; Moliva, Melina Vanesa; Serral, Federico; Fernandez Do Porto, Darío; Reinoso, Elina B. (Elsevier, 2025)
Environmental bacteria, such as streptococci and enterococci, play an important role in bovine mastitis. This study aims to characterize the genome sequence of Enterococcus spp. isolated from a case of subclinical mastitis. Genomic DNA was isolated and sequenced using Illumina and Oxford Nanopore platforms. Final genome was assembled in a single circular chromosome and one plasmid comprising 2.556.630 bp (GC% 38.60) and 150.514 bp (GC 36 %), respectively. Phylogeny confirmed that strain SU-B46 is closely related to E. lactis reference genomes. The alignment confirmed the presence of E. lactis. Additionally, the genomic analysis identified twelve potential virulence genes related to adhesion, immune evasion and biofilm formation among others, but none were found in the plasmid. The strain exhibited resistance to aminoglycosides, macrolides and glycopeptides. This study presents the first report of an E. lactis strain isolated from a subclinical mastitis case in Argentina, broadening the geographical and host range of this pathogen. These findings suggest the possible involvement of E. lactis as an etiological agent of bovine mastitis. Further studies are needed to understand the significance of this agent, warranting additional investigation to ensure its optimal management, especially within the dairy industry.